A method for analysis of maritime transportation systems in the life cycle approach – The oil tanker example. (15th November 2017) - Nian, Victor; Yuan, Jun
Highlights: We proposed a life cycle analysis method for examining systems providing services. We applied the method to evaluate life cycle carbon emissions of maritime transport. Findings suggest 12 knots as a reference speed for optimum energy/carbon efficiency. A reference range of life cycle carbon emission factors of oil shipping is reported. Abstract: The International Maritime Organization considers decarbonizing international shipping an important and necessary step towards a sustainable global trade economy. There have been commendable studies focusing on nearly all stages of maritime transport from shipbuilding, to operation and maintenance, to engine performance optimization, to fuel options, and to dismantling and recycling, but the number of whole system level life cycle analyses (LCA) on maritime transport is far less than that on energy and goods production. This scarcity highlights the need for more independent studies to enrich the LCA literature on shipping. In response, we propose a method that adapts existing methods for the analysis of energy and goods producing systems. This approach provides crucial continuity in the serial development of a generic process chain analysis framework to ensure consistency in system and boundary formulations. Findings from the case study suggest that "slow-steaming" may not always be desirable and that 12 knots could be considered as a reference optimum speed for tankers of all size categories. Cruising at 12 knots over selected routes between top oil import and export countries, a reference range of life cycle carbon emission factors is found to be 6–9 mg of carbon dioxide for moving 1 tonne of crude oil over 1 km distance (mg-CO2 /t-km). These developments demonstrate the ability of the proposed method to provide independent assessments on the life cycle carbon emissions of maritime transport systems and to derive new and/or alternative insights on the decarbonizing measures conceived by earlier studies.